Native language interference in learning english as a foreign language: an analysis of written material produced by spanish speaking students in senior high school classes. - Velasco, Gilda (2010)
he evolving development of human race and societies themselves have had different factors that allowed their progress, one of these factors was language formation. History tells us, that the first societies settled down in wide ranges of territory and this settlement created the necessity to establish cultural patterns that made possible the adequate communication within the group. The most important cultural pattern developed was language, an own linguistic code system common for that group only.